New TDOA‐Based Three‐Dimensional Positioning Method for 3GPP LTE System. Issue 2 (1st April 2017) - Lee, Kyunghoon; Hwang, Wonjun; Ryu, Hyunseok; Choi, Hyung‐Jin
Abstract : Recently, mobile positioning enhancement has attracted much attention in the 3rd generation partnership project long‐term evolution system. In particular, for urban canyon environments, the need for three‐dimensional (3D) positioning has increased to enable the altitude of users to be measured. For several decades, several time difference of arrival (TDOA‐) based 3D positioning methods have been studied; however, they are only available when at least four evolved Node Bs (eNBs) exist nearby or when all eNBs have the same height. Therefore, in this paper, we propose a new 3D positioning method that estimates the 3D coordinates of a user using three types of two‐dimensional (2D) TDOAs. However, the give inaccurate results owing to the undefined axis of the 2D coordinate plane. Therefore, we propose a novel derivation of the hyperbola equation, which includes the undefined axis coordinate in the 2D hyperbola equation. Then, we propose an interaction algorithm that mutually supplies the undefined axis coordinate of users among 2D TDOAs. By performing extensive simulations, we verify that the proposed method is the only solution applicable by using three eNBs with different heights.